Aligning islamic education management with the sdgs: Institutional transformation, policy coherence, and value-based leadership - Hamdanah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study examines how Islamic educational institutions align their governance, policy frameworks, and leadership practices with the Sustainable Development Goals (SDGs), focusing particularly on institutional transformation and policy coherence. Using an interpretivist qualitative design, the research explores three contrasting Islamic educational settings—a pesantren-based higher education institution, a modern Islamic university, and an urban madrasah—to understand how global development principles are translated into locally grounded practices. Data were generated through semi-structured interviews, document analysis, and observations of governance processes. The findings reveal that Islamic educational institutions possess strong ethical foundations that naturally support principles of sustainability, human dignity, and social responsibility. Alignment with the SDGs becomes effective when institutions reinterpret their core values within a global vocabulary rather than treating the SDGs as external obligations. Policy coherence emerges as a critical condition for meaningful progress, enabling institutions to move beyond fragmented initiatives toward integrated and strategic reform. Equally important is the presence of value-based leadership capable of balancing tradition with innovation, guiding institutions through cultural, administrative, and pedagogical transitions. Despite these strengths, challenges remain, including limited leadership capacity in some contexts, gaps in curriculum integration, and the need for improved monitoring systems. Nevertheless, the study concludes that Islamic educational institutions hold substantial potential to contribute to the SDGs through a governance approach that harmonises ethical heritage with contemporary developmental aims. Their engagement with the SDGs demonstrates how local educational traditions can enrich global aspirations for inclusive and sustainable education.